The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1289/ehp.0901716
|View full text |Cite
|
Sign up to set email alerts
|

Urinary, Circulating, and Tissue Biomonitoring Studies Indicate Widespread Exposure to Bisphenol A

Abstract: BackgroundBisphenol A (BPA) is one of the highest-volume chemicals produced worldwide, and human exposure to BPA is thought to be ubiquitous. Thus, there are concerns that the amount of BPA to which humans are exposed may cause adverse health effects. Importantly, results from a large number of biomonitoring studies are at odds with the results from two toxicokinetic studies.ObjectiveWe examined several possibilities for why biomonitoring and toxicokinetic studies could come to seemingly conflicting conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
609
6
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,064 publications
(663 citation statements)
references
References 126 publications
20
609
6
10
Order By: Relevance
“…In neonatal rhesus monkeys gestationally exposed to BPA via food, a significantly higher density of mammary buds and an overall greater development of mammary epithelium was observed in newborns (Table 1). 27 Although the treatment dose of 400 µg kg –1 BW day –1 was high, the mean concentration of unconjugated BPA in maternal serum was 0.68 ng mL –1 , similar to what is measured in humans 98. A study in Wistar‐Furth rats revealed that fetal exposure to BPA (2.5, 25, 250, 1000 µg kg –1 BW day –1 ) via an implanted osmotic pump resulted in a 3–4 fold increase in the number of hyperplastic ducts at postnatal day (PND) 50 at all doses, and led to a significantly elevated number of these structures at PND90 at only the lowest dose 25.…”
Section: Epidemiological Animal and In Vitro Evidence Of Bpa‐associsupporting
confidence: 65%
“…In neonatal rhesus monkeys gestationally exposed to BPA via food, a significantly higher density of mammary buds and an overall greater development of mammary epithelium was observed in newborns (Table 1). 27 Although the treatment dose of 400 µg kg –1 BW day –1 was high, the mean concentration of unconjugated BPA in maternal serum was 0.68 ng mL –1 , similar to what is measured in humans 98. A study in Wistar‐Furth rats revealed that fetal exposure to BPA (2.5, 25, 250, 1000 µg kg –1 BW day –1 ) via an implanted osmotic pump resulted in a 3–4 fold increase in the number of hyperplastic ducts at postnatal day (PND) 50 at all doses, and led to a significantly elevated number of these structures at PND90 at only the lowest dose 25.…”
Section: Epidemiological Animal and In Vitro Evidence Of Bpa‐associsupporting
confidence: 65%
“…Among the frequent human exposed EDCs, bisphenol A (BPA) is one of the highest production volume chemicals worldwide [6]. BPA is widely used to produce polycarbonates and epoxy resins, which are in the raw materials of buckets, feeding bottles, food cans and packaging [7], resulting in various opportunities for human exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions: Known dietary sources of BPA exposure explained less than half the variability in uBPA levels, regardless of diet assessment method. Findings suggest that a questionnaire approach may be insufficient for ranking BPA exposure level and additional important sources of BPA exposure likely exist.Bisphenol A (BPA), used in the manufacture of polycarbonate plastics and epoxy resins, is one of the highest-volume chemicals produced worldwide (1,2) and production is predicted to reach more than 4·09 Mt (9 billion lb) by 2020 (3) . Biomonitoring data indicate widespread, chronic low-level exposure to BPA (2,(4)(5)(6) .…”
mentioning
confidence: 99%
“…Bisphenol A (BPA), used in the manufacture of polycarbonate plastics and epoxy resins, is one of the highest-volume chemicals produced worldwide (1,2) and production is predicted to reach more than 4·09 Mt (9 billion lb) by 2020 (3) . Biomonitoring data indicate widespread, chronic low-level exposure to BPA (2,(4)(5)(6) .…”
mentioning
confidence: 99%
See 1 more Smart Citation